Current issues of pedagogy and psychology - Prokopev N. I., Ananev V. N., Ponomareva L. I., Gurtovoi E. S., Novoselov K. A., Orekhova S. E., Sivak O. A., Shevtsova A. V., Kudriashova S. K., Kudriashov V. I., Gamalienko A. B., Saenko N. V., Piatibratova I. V., Iakusheva O. V., Aleksina T. V., Aleksandrov S. G., Zenkina V. G., Solodkova O. A., Bozhko G. G., Agibalova A. A., Andreeva O. S., Koreneva A. V., Veretennikova N. D., Koreneva A. V., Kalmykov V. A., Ladukhina N. R., Iagudin V. S., Arzamasova E. L., Gani S. V., Konstantinova N. I., Glotova G. A., Shipilova E. S., Krasnova S. G., Kachalov V. I., Stepanov A. N., Kharlamova K. E. (Current issues of pedagogy and psychology, 2025)
the chapter examines the influence of musical compositions on the patriotism of the younger generation, as part of a survey conducted among a number of university students in Kazan, on the basis of which the influence of patriotic songs on the emergence of the spirit of unity and pride in their country was revealed. Musical compositions play a significant role in the formation of patriotic feelings among the younger generation. In the context of globalization and cultural diversity, it is important to study how music can contribute to strengthening national identity and cohesion. Research on this topic is relevant, as it helps to understand the mechanisms of music's impact on young people and its role in fostering civic qualities.
Keywords: патриотизм; общество; единство; unity; society; Patriotism; гордость; музыкальное произведение; musical work; pride